Social media communication: content analysis of Indonesian parliament instagram account - Jamil, Achmad; Eriyanto (Jurnal Studi Komunikasi, 2021)
This study aimed to analyse the dialogic communication by The House of Representatives through Instagram of the Republic of Indonesia (DPR-RI) as part of public institutions. This study is prompted by the low public trust in DPR using dialogic communication in Instagram. DPR-RI Instagram account is one of the most popular accounts among Indonesian government bodies’ Instagram accounts. Having 470,000 followers, DPR_RI’s Instagram has uploaded 6,347 photos and videos. The research method used was quantitative content analysis. This study also used thematic units that examined the topic or discussion of a text. The populations in this study were the posts on the Instagram account of DPR RI (@dpr_ri) from January 2015 to December 2020. The sample in this study amounted to 600 posts where, in each year, 100 posts were taken as a sample. The result indicates that DPR Instagram account has not applied the principle of dialogic communication. The low number of posts suggesting a dialogue with the public and stakeholders signifies this finding. DPR could use the results of this study to improve their public communication, especially in the use of social media.